STUDY THE CHARACATERISTIC OF SOILS TO DETERMINE SOME TYPES OF LANDS DEGRADATION FOR MAHMUDIYA DISTRICT (Journal of the College of Education for Women, 2019)
This study comprised three traverses extending parallel through the Northern, Central and Southern Mahmudiya districts, and perpendicular to the course of the Euphrates River. They were identified to collect (15) soil samples and some water samples as distributed within the land cover classes of the study area. Those classes were determined by visual interpretation and supervised classification for Landsat (TM) images obtained in August/2007. The digital classification was based on Maximum Likelihood method using six spectral bands excluding the thermal band. Chemical and physical laboratory analysis for the soil characteristics was performed to determine the types of land degradation in the study area.The results showed that the highest percentage of degradation is related to the chemical degradation type having a percentage of (85.71%). It is distributed in the land areas of very height values of calcium carbonate, salinity and alkaline contents, with low values of organic material, total nitrogen and phosphorus. In the other hand the percentage of the physical degradation type was (14.29%) due to higher values of bulk density.